2008
DOI: 10.2337/dc08-1171
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, Sulfonylureas, or Other Antidiabetes Drugs and the Risk of Lactic Acidosis or Hypoglycemia

Abstract: OBJECTIVE -Lactic acidosis has been associated with use of metformin. Hypoglycemia is a major concern using sulfonylureas. The aim of this study was to compare the risk of lactic acidosis and hypoglycemia among patients with type 2 diabetes using oral antidiabetes drugs. RESEARCH DESIGN AND METHODS-This study is a nested case-control analysis using the U.K.-based General Practice Research Database to identify patients with type 2 diabetes who used oral antidiabetes drugs. Within the study population, all incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
262
4
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(296 citation statements)
references
References 25 publications
22
262
4
8
Order By: Relevance
“…Fortunately, a nonclinical report at the 75th Scientific Sessions of the American Diabetes Association that studied the relationship between systemic metformin exposure and increased plasma lactate concentrations shows that intragastric administration of metformin (300 mg/kg) does not increase blood levels of lactic acid in normoglycemic rats 53. Two other large clinical studies have also demonstrated that there is no difference in the incidence of lactic acidosis between metformin‐ and non–metformin‐treated groups 54, 55. Herein, our data also demonstrate that the dosage of metformin used in the study is safe and does not cause hypoglycemia and lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, a nonclinical report at the 75th Scientific Sessions of the American Diabetes Association that studied the relationship between systemic metformin exposure and increased plasma lactate concentrations shows that intragastric administration of metformin (300 mg/kg) does not increase blood levels of lactic acid in normoglycemic rats 53. Two other large clinical studies have also demonstrated that there is no difference in the incidence of lactic acidosis between metformin‐ and non–metformin‐treated groups 54, 55. Herein, our data also demonstrate that the dosage of metformin used in the study is safe and does not cause hypoglycemia and lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…It decreases basal glucose output by suppressing gluconeogenesis and glycogenolysis in the liver and by increasing glucose uptake in muscle tissue. Because metformin does not directly stimulate insulin secretion, the risk of hypoglycemia associated with its use is lower than that associated with the use of other oral antidiabetes drugs (12). The molecular mechanism of metformin involves liver kinase B1-dependent activation of AMP-activated protein kinase (AMPK; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as evidenced by Bodmer et al, the highest risk of hypoglycaemia is present during insulin treatment (14.9%) [28]. As to the risk of oral drugs, it was 1% and 2.86%, for metformin and sulphonylureas respectively.…”
Section: Discussionmentioning
confidence: 93%